Inhibiting H3K27 Demethylases Downregulates CREB‐CREBBP, Overcoming Resistance in Relapsed Acute Lymphoblastic Leukemia - Juan Lazaro‐Navarro; Clara Alcon; Mathurin Dorel; Lina Alasfar; Lorenz Bastian; Claudia Baldus; Kathy Astrahantseff; Marie‐Laure Yaspo; Joan Montero; Cornelia Eckert (Cancer Medicine)
ABSTRACT Background CREB binding protein (CREBBP) is a key epigenetic regulator, altered in a fifth of relapsed cases of acute lymphoblastic leukemia (ALL). Selectively targeting epigenetic signaling may be an effective novel therapeutic approach to overcome drug resistance. Anti‐tumor effects have previously been demonstrated for GSK‐J4, a selective H3K27 histone demethylase inhibitor, in several animal models of cancers. Methods To characterize the effect of GSK‐J4, drug response profiling, CRISPR‐Dropout Screening, BH3 profiling and immunoblotting were carried out in ALL cell lines or patient derived samples. Results Here we provide evidence that GSK‐J4 downregulates cyclic AMP‐responsive element‐binding protein (CREB) and CREBBP in B‐cell precursor‐ALL cell lines and patient samples. High CREBBP expression in BCP‐ALL cell lines correlated with high GSK‐J4 sensitivity and low dexamethasone sensitivity. GSK‐J4 treatment also induced Bcl‐2 and Bcl‐XL dependency and apoptosis. Conclusions This study proposes H3K27 demethylase inhibition as a potential treatment strategy for patients with treatment‐resistant ALL, using CREBBP as a biomarker for drug response and combining GSK‐J4 with venetoclax and navitoclax as synergistic partners.